A exclusão dentro da exclusão: trajetórias negras em busca da educação (Assentamento Nova Vida - Upanema/RN) - Farias, Ana Paula Campos de (Universidade Federal Rural do Semi-Árido, 2021)
This study addresses a proposal for reflection on situations of social exclusion, with a view to the specific intersectionalities of the researched place. The locus of the study is the Nova Vida Settlement, which is located twenty-three miles from the city of Upanema / RN. Brazil has been carrying out actions to confront the Agrarian Reform for more than two decades, with public policies intensifying with the references of social movements. In this reality, the settlement model that was researched is composed. A field research is about the social and school exclusion of sectors already socially excluded and focuses on the relationship between residents of a street located in PA Nova Vida, called Rua dos Negros (Rua João José da Silva) and residents of the other streets of the PA Nova Vida community. Faced with so many inquiries, a qualitative research emerges, where it was carried out in three moments, using the techniques of questionnaires with open and closed questions and shown. With the general objective of understanding the exclusion processes along the school trajectory of black people in agrarian reform settlements. And as specific objectives: To analyze with the Nova Vida, Upanema / RN community the social aspects that involve factors such as: racial ethnic discrimination and Reflect as situations that permeate between community life and school. For this group that lives on Rua dos Negros, is there social exclusion on the part of/the residents/the other streets? Do these people isolate themselves by defense or defense, creating a kind of mutual distance from the other residents/as? To analyze this phenomenon and the consequences in the subject's life, he brought Norbert Elias (2000), Neusa Santos (1983), Roseli Caldart (2000), Abdias do Nascimento (1980), Paulo Freire (1979) and Chizzotti (2006). The data collected were the following years: first in 2016, 2019 and 2021, with the participation of residents of Rua dos Negros and the community in general. Initially, the objective was to understand the organization of Rua dos Negros, the participation in the social and school life of the settlement, and with the deepening of the readings, some questions were answered.
Keywords: Reforma Agrária; Negros; Exclusão social; Nova Vida; Oeste Potiguar; Agrarian Reform; Blacks; Social exclusion; New life; West Potiguar; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL